1986
DOI: 10.1111/j.1476-5381.1986.tb10272.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of noradrenaline, B‐HT 920, methoxamine, angiotensin II and vasopressin on mean circulatory filling pressure in conscious rats

Abstract: 1 The effects of vasoactive substances on mean circulatory filling pressure (MCFP), an index of total body venous tone, were determined in conscious rats.2 Cumulative doses of saline (0.9% w/v NaCl solution), methoxamine (xl-adrenoceptor agonist), B-HT 920 (a2-adrenoceptor agonist) noradrenaline and vasopressin, and individual doses of angiotensin II (AII), were infused into the rats. Mean arterial pressure (MAP), MCFP and heart rate (HR) were determined before and during the plateau responses to infusions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 23 publications
2
22
0
Order By: Relevance
“…It has previously been shown by Guyton et al that infusion of epinephrine significantly increases Pmsf to a plateau value around 16 mmHg (8). This has been confirmed experimentally by numerous authors who have shown in animals that norepinephrine and other ␣-adrenoreceptor agonists increase Pmsf (18,21,29). The reason why we found a slight inverted relation between age and Pmsf is unclear but remains to be confirmed since only 19 patients of our cohort were Ͻ50 years old.…”
Section: Discussionsupporting
confidence: 71%
“…It has previously been shown by Guyton et al that infusion of epinephrine significantly increases Pmsf to a plateau value around 16 mmHg (8). This has been confirmed experimentally by numerous authors who have shown in animals that norepinephrine and other ␣-adrenoreceptor agonists increase Pmsf (18,21,29). The reason why we found a slight inverted relation between age and Pmsf is unclear but remains to be confirmed since only 19 patients of our cohort were Ͻ50 years old.…”
Section: Discussionsupporting
confidence: 71%
“…noradrenaline, angiotensin II as well as angiotensin III (Pang & Tabrizchi, 1986;Tabrizchi & Pang, 1987; were found in similar studies in our laboratory to raise MAP and MCFP dose-dependently. Therefore, the absence of a rise in MCFP in the present study is not due to a lack of sensitivity of the technique to detect changes.…”
Section: Discussionsupporting
confidence: 50%
“…Prazosin was also found to reduce MCFP in an anesthetized, open-chest dog preparation, but only during infusion of norepinephrine (Ito and Hirakawa, 1984). Selective ␣ 1 -adrenergic agonists produce little increase in MCFP when infused into intact rats, whereas norepinephrine produces a potent, dose-dependent increase in MCFP (Pang and Tabrizchi, 1986). Studies in isolated mesenteric veins confirm that activation of ␣ 1 -adrenergic receptors may be necessary to observe a venoconstrictor effect of ␣ 2 -adrenergic receptors in some vascular beds.…”
mentioning
confidence: 54%